Re-Reading Mary Wroth
XIII, 298 p. 5 illus.
Keywords: Approaching the writings of Mary Wroth through a fresh 21st-century lens, this volume accounts for and re-invents the literary scholarship of one of the first "canonized" women writers of the English Renaissance. Essays present different practices that emerge around "reading" Wroth, including editing, curating, and digital reproduction.